Amelioration of thermal storage system with inclusion of nanomaterial within solidification. (February 2023) - Li, Z.; Leng, Jiaxuan; Talabany, Ziyad Jamil; Othman, Hakeem A.; Khalifa, Narjes Turki; Moniem, Ashraf A.; Hussin, Amira M.
Abstract: In this study, three fins with rectangular shapes have been mounted within an elliptic enclosure to create a new thermal system. Numerical method for analyzing discharging of PCM inside the mentioned geometry has been scrutinized. With neglecting the low amount of velocity for liquid phase, the mathematical model has been derived for this problem. The conduction has a main role in solidification and loading nanoparticles within water can lead to better performance. Concentration and shapes of powders were active parameters of modeling. Low deviation of outputs with the previous article indicated good accuracy of modeling. With an augmenting shape factor, the period declines less than 7 % and augmenting concentration can reduce the period by about 26.81 %. The period for cases with water as PCM is 1.36 times bigger than that of NEPCM. The shortest period takes 728.16 s to reach full solidification. Highlights: Three fins with rectangular shapes have been mounted within storage system. With an augmenting shape factor, the period declines less than 7 %. The period for cases with water as PCM is 1.36 times bigger than that of NEPCM.